Frequency-Dependent Magnetic Susceptibility of Sediments of Lake Tondano, Minahasa, North Sulawesi - Vistarani Arini Tiwow; Meytij Jeanne Rampe; Ishak Pawarangan; Muhammad Arsyad; Sayenne Givenshe Pungus; Gita Gratia Patris Nangka; Igreya Mitchell Kumendong; Oksan Prasetio Mundiahi (Sam Ratulangi University, Manado, Indonesia, 2026)
A study has been conducted on frequency-dependent magnetic susceptibility in sediments of Lake Tondano, Minahasa, North Sulawesi. This study aims to analyze the types of minerals, grain sizes, and magnetic domains in sediment samples of Lake Tondano. The method used is the rock magnetism method, specifically the magnetic susceptibility parameters. Magnetic susceptibility measurements used a Bartington susceptibility meter that works at two frequencies, namely 470 Hz and 4700 Hz. The results obtained are sediment samples are indicated to contain ferrimagnetic minerals. The grain size distribution in sediment samples is predominantly fine <0.03 µm. The frequency-dependent magnetic susceptibility value χFD% is dominantly more than 2%, indicating the magnetic domain in sediment samples of Lake Tondano are a mixture of superparamagnetic (SP) and single-stable-domain (SSD). Keywords: Magnetic domains; magnetic minerals; lake sediments; magnetic susceptibility; magnetic grain size